Enhancement the Sensitivity of Humidity Sensor Based on an Agarose Coating Transmission-Type Photonic Crystal Fiber Interferometer - Hassan, Hassan F.; Taher, Hanan J. (Iraqi Journal of Laser, 2017)
Photonic Crystal Fiber Interferometers (PCFIs) are widely used for sensing applications. This work presents the fabrication and the characterization of a relative humidity sensor based on a polymer-coated photonic crystal fiber that operates in a Mach- Zehnder Interferometer (MZI) transmission mode. The fabrication of the sensor involved splicing a short (1 cm) length of Photonic Crystal Fiber (PCF) between two single-mode fibers (SMF). It was then coated with a layer of agarose solution. Experimental results showed that a high humidity sensitivity of 29.37 pm/%RH was achieved within a measurement range of 27–95%RH. The sensor also showed good repeatability, small size, measurement accuracy and wide humidity range. The RH sensitivity of the sensor has a significant dependence on the thickness of the coating and the sensor with the highest sensitivity showed a linear response for RH change in the range of 27-95% RH and a fast response time of 0.8 sec for an RH change from 50% to 90%.